The impact of Psoriatic Arthritis on sleep quality and mood swings (Research, Society and Development, 2025)
Introduction: Psoriatic arthritis (PsA) is a chronic inflammatory disease that affects the joints and is associated with patients with cutaneous psoriatic disease (PD). Sleep quality is often impaired in patients with PsA, negatively impacting their quality of life. Objective: To evaluate sleep quality in patients diagnosed with PsA and treated at a rheumatology outpatient clinic in the metropolitan region of Belém do Pará. Methods: This is a descriptive and observational study that included 13 patients with a confirmed diagnosis of PsA. A standardized protocol was used to collect data from patient records. Results and discussion: The epidemiological profile corresponds to non-white women, between 61 and 70 years of age, from the metropolitan region of Belém. Their diagnoses were attributed more than 10 years ago, they present as the main comorbidity associated with Systemic Arterial Hypertension and use secukinumab as the main medication. The most prevalent initial clinical manifestation was joint or cutaneous, with secondary lesions appearing after 1 to 5 years, with morning stiffness lasting more than 30 minutes and pain between 5 and 6 on the visual scale. In addition, sleepiness was scored as normal by the Epworth sleep scale, with good sleep quality on the Pittsburgh Sleep Quality Index, presence of OSAS on the Berlin Questionnaire, and probable depression and/or anxiety on the HAD scale. Conclusions: The results highlight the influence of PsA on quality of life.